Effects of thermal treatments on the stability of trans-resveratrol and yeast inactivation in trans-resveratrol-amplified grape juice - Lee Dong-Un (Archives of Biological Sciences, 2014)
For the production of trans-resveratrol-amplified grape juice, both trans-resveratrol quantity and microbial quality are important for the functionality and shelf life of the juice. Therefore, the thermal stability of trans-resveratrol and thermal inactivation of Saccharomyces cerevisiae within the grape juice was investigated at 60°C, 80°C and 100°C. Inactivation of S. cerevisiae was fitted to first-order kinetics, and the inactivation rate (k1) and decimal reduction time (D-value) at each treatment temperature were estimated. The control grape juice had an inactivation rate of 0.0014 (s-1) and a D-value of 11.90 min at 60°C, whereas the trans-resveratrol-amplified grape juice had an inactivation rate of 0.0016 (s-1) and a Dvalue of 10.42 min at the same temperature. Similar inactivation kinetics of the control and trans-resveratrol-amplified grape juice were observed at 80°C and 100°C, which indicates that increased trans-resveratrol content does not affect the thermal inactivation of inoculated S. cerevisiae.